Mutants of Arabidopsis thaliana Capable of Germination under Saline Conditions. - Saleki, R. (1993)
Three mutant strains of Arabidopsis thaliana var Columbia were selected for their ability to germinate in elevated concentrations of NaCl. They were not more tolerant than wild type at subsequent development stages. Wild-type strains could not germinate at concentrations > 125 mM NaCl. Two of mutant strains, RS17 and RS20, could withstand up to 225 mM, whereas RS19 was resistant to 175 mM. The RS mutants could also germinate under even lower osmotic potentials imposed by high concentrations of exogenous mannitol (550 mM), whereas the effects of elevated levels of KCl, K2SO4, and LiCl were similar among the mutants and wild type. Therefore, the mutants are primarily osmotolerant, but they also possess a degree of ionic tolerance for sodium. Sodium and potassium contents of seeds exposed to high salinities indicated that the NaCl-tolerant mutants absorbed more of these respective cations during imbibition. These higher internal concentrations of potassium and sodium could contribute to the osmotic adjustment of the germinating seeds to the low osmotic potential of the external medium. Genetic analysis of F1 and F2 progeny of outcrosses suggest that the salt-tolerant mutations are recessive and that they define three complementation groups.